The Influence Of Return On Asset, Debt To Equity Ratio And Current Ratio Toward Stock Price In Consumer Goods Industry Listed On Indonesia Stock Exchange - Andoko, Andoko; Winson, Lelita (Journal of Industrial Engineering & Management Research, 2021)
Consumer goods industry has been growing throughout the years to fulfil the demand from the ever-growing Indonesian population. Good management is important in order to thrive and succeed in the consumer goods industry, for such is the investing decision. It is a good opportunity in earning source of finance when an investor purchase shares with the intention to obtain profits from the increasing share price, making it important to know and understand how to choose and making the right decision. This research is conducted with the purpose to find out the influence of three chosen independent variable of return on asset, debt to equity ratio and current ratio toward stock price as the dependent variable. This research is conducted using the quantitative research along with the purposive sampling method. Data used in this research is the secondary data taken from Indonesia Stock Exchange with 29 eligible companies from year 2017 to 2020, which totaled to 116 data assessed. Based on the result of the research conducted, return on asset has a significant influence on the stock price while both debt to equity ratio and current ratio have no significant influence on the stock price in consumer goods industry listed on Indonesia Stock Exchange for the year 2017-2020. According to the findings of the research, the three chosen independent variables have a very low influence towards the stock price.